2022
DOI: 10.1186/s40035-022-00305-1
|View full text |Cite
|
Sign up to set email alerts
|

Defective mitophagy and the etiopathogenesis of Alzheimer’s disease

Abstract: Accumulation of impaired mitochondria and energy metabolism disorders are non-negligible features of both aging and age-related neurodegeneration, including Alzheimer’s disease (AD). A growing number of studies suggest that mitophagy disorders play an important role in AD occurrence and development. The interaction between mitophagy deficits and Aβ or Tau pathology may form a vicious cycle and cause neuronal damage and death. Elucidating the molecular mechanism of mitophagy and its role in AD may provide insig… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
16
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 20 publications
(17 citation statements)
references
References 118 publications
1
16
0
Order By: Relevance
“…Since mitophagy integrity is important in maintaining neural function, we examined mitophagic flux. We found that C. elegans treated with olanzapine had a low mitophagic flux, supporting the idea that neural lesion is associated with mitophagy deficits (Zeng et al., 2022). Together, these results highlight that defective mitophagy may contribute to neuronal deficits, leading to cognitive decline.…”
Section: Discussionsupporting
confidence: 87%
“…Since mitophagy integrity is important in maintaining neural function, we examined mitophagic flux. We found that C. elegans treated with olanzapine had a low mitophagic flux, supporting the idea that neural lesion is associated with mitophagy deficits (Zeng et al., 2022). Together, these results highlight that defective mitophagy may contribute to neuronal deficits, leading to cognitive decline.…”
Section: Discussionsupporting
confidence: 87%
“…In Alzheimer's disease, Aβ1‐40 induced pericyte mitophagy through the PINK1/Parkin pathway 52 . Under physiological conditions, PINK1 is transported to the inner mitochondrial membrane (IMM) and degraded by presenilin‐associated rhomboid‐like protease (PARL) 53 . However, in damaged mitochondria, the degradation of PINK1 is inhibited to maintain PINK1 present on the outer mitochondrial membrane (OMM) 54 .…”
Section: Discussionmentioning
confidence: 99%
“…Our KEGG pathway enrichment analysis showed that autophagy, mitophagy, and metabolic pathways are the most affected in both UNC93A and WDR27 inhibitory conditions. Interestingly, these pathways play an important role in Aβ clearance, and thus dysfunction may lead to the development of Alzheimer’s disease ( Zeng et al, 2022 ). As reduced autophagy activity was related to increased cell death in response to intracellular stress ( Galati et al, 2019 ), these variants could have a negative effect on BBB integrity.…”
Section: Discussionmentioning
confidence: 99%